Etika Bisnis dan Kualitas Produk terhadap Loyalitas Nasabah Bank BPR Lengayang - Susanti, Febri; Lestari, Vivi Eka Widya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to determine business ethics and product quality on customer loyalty at Bank BPR Lengayang. This research is a quantitative research, the sampling method uses the Slovin formula with a total of 100 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results of this research show that business ethics has a positive and significant effect on customer loyalty with a t-count greater than t-table (4.265 > 1.671), and product quality has a positive and significant effect on customer loyalty with a t-count greater than t- table (4,504 > 1,671).